ANALYSIS OF GENDER EQUALITY: THE ROLE WOMEN IN TEACHINGS AND PRACTICES OF SIKHISM IN MEDAN CITY - Mutiara, Indah; Desky, Ahmed Fernanda (Jurnal Sosiologi Dialektika Sosial, 2024)
This research aims to analyze gender equality in the teachings and practices of Sikhism in Medan City. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with key informants, participant observation, and document analysis. The research results show that the teachings of Sikhism emphasize gender equality between men and women. This is reflected in various Sikh sacred texts, such as the Guru Granth Sahib Ji, which contains stories and teachings about strong and inspiring women. Sikh teachings and practices in Medan demonstrate a strong commitment to gender equality. These Sikh principles are in line with Simone De Beauvoir's feminist theory, she emphasizes and encourages that women must believe they have equal rights and abilities to manage their own lives. and the Sikh Religion in Medan is active in realizing gender equality through various programs and activities. It is important to note that this analysis only provides a brief overview of the role and position of women in Sikh teachings and practices in Medan through the lens of feminist theory. These challenges include patriarchy that still exists in society, gender stereotypes, and women's lack of access to education and economic opportunities. This research recommends several efforts to improve gender equality in the Sikh Religion in Medan. These efforts include education about gender equality, women's empowerment, and increasing women's participation in various aspects of life in society.